The effect of airline's ESG management on corporate reputation, corporate image, and relationship continuance intention - Yunyoung Kim; Wooje Cho (Global Business & Finance Review (GBFR), 2024)
Purpose: This study aims to investigate the impact of airline ESG management on corporate reputation, corporate image, and relationship continuance intention of domestic airlines. Design/methodology/approach: The data for this study were collected by distributing 300 self-completion ques- tionnaires online, and a total of 211 questionnaires were collected, and 201 questionnaires, excluding 10 non-re- sponses, were used for empirical analysis. Frequency analysis, exploratory factor analysis, reliability analysis, and regression analysis were conducted to test the hypotheses of the study. Findings: Among the ESG management factors of airlines, this study found that environment and governance had a significant positive impact on corporate image and relationship continuance intention. The study also found that social and corporate governance had a significant positive effect on corporate reputation. Research limitations/implications: This study is limited by the fact that the data was collected only from domestic travelers. In addition, there may be differences in ESG management activities between FSCs and LCCs, so a follow- up study is needed to extend this study and compare the differences in ESG management between FSC and LCC. Originality/value: Given the lack of research on airline ESG management, this study analyzes the factors of airline ESG management and demonstrates the importance of ESG management by evaluating companies from a consumer perspective. It also identifies the relationship between airline ESG management and corporate reputation, corporate image, and relationship continuance intention from a corporate marketing perspective, and suggests effective meas- ures for airlines to achieve sustainable growth.
Keywords: 650; Airline industry; ESG management; Corporate reputation; Corporate image; Relationship continuance intention